Hardware/software co-design of H.264/AVC encoders for multi-core embedded systems - Dias, Tiago (2020)
This paper presents a multi-core H.264/AVC encoder suitable for implementations in small and medium complexity embedded systems. The proposed structure results from an efficient hardware/software co-design methodology, where the encoder software application is highly optimized and structured in a very modular and efficient manner, so as to allow its most complex and time consuming operations to be offloaded to dedicated hardware accelerators. The considered methodology adopts a simple and efficient core interconnection mechanism to easily allow the inclusion and the removal of such optimized processing cores. Experimental results obtained with the implementation in a Virtex4 FPGA of an H.264/AVC encoder using an ASIP IP core as a ME hardware accelerator have proven the advantages of this methodology. For the considered system, speedup factors greater than 15 were obtained with a very modest increase of the involved hardware resources.